Pelatihan Pembuatan Hantaran Sebagai Pengembangan Kreativitas untuk Menumbuhkan Potensi Kewirausahaan PKK Desa Randupitu Kecamatan Gending Kabupaten Probolinggo - Mastina Maksin; Abir Afifah S; A. Rizqi Hidayatullah; Citra Agustin Purnama; M. Adi Prasetyo; Shinta Dwi Pramudya; Sofiya Trida Nur Aini (CV. ITTC INDONESIA, 2024)
Training is a series of activities that are structured in a targeted manner to improve skills, experience, expertise, increase knowledge and change an individual's attitude (Rozalena and Dewi in Nugroho, 2019). Development is a consequence of the results of education and training which is interpreted as preparing individuals to take responsibility for improving and enhancing knowledge, attitude skills, and personality traits (Rozalena and Dewi in Nugroho, 2019). Creativity is the ability to produce new ideas, new concepts, or original and valuable solutions (Wardana, 2023). This involves the ability to think outside the box, make new connections between concepts, and see problems from different perspectives. The purpose of this training is to develop entrepreneurial talent and train the skills of PKK members so that they can generate profits or additional income that can be put into the PKK treasury, namely by making deliveries. This study uses a qualitative descriptive method by explaining how community empowerment training for PKK members develops potential in entrepreneurship. So that in this case it is explained more clearly and coherently regarding the results of the implementation. This training was conducted in the Randupitu Village Secretariat Room and involved PKK cadre mothers. The results of the study showed that this training succeeded in improving the skills and motivation of PKK members in making creative and marketable gifts, which can provide additional income for them and contribute to the PKK cash. This training also encouraged PKK members to innovate and be independent in meeting market demand.